Acupressure and Cognitive Training Can Improve Cognitive Functions of Older Adults With Mild Cognitive Impairment: A Randomized Controlled Trial - Sun, Jingxian; Zeng, Hui; Pan, Lu; Wang, Xiaosong; Liu, Mengjiao (Frontiers in Psychology, 2021)
Background: Given the limited effectiveness of pharmacological treatments in mitigating cognitive decline in individuals with mild cognitive impairment (MCI), there is a pressing need for developing effective non-pharmacological intervention programs to counteract MCI-related cognitive decline. Acupressure and cognitive training are safe and cost-effective; however, evidence of the effect of acupressure or the combined effect of acupressure and cognitive training on cognitive functions of older adults with MCI is limited. Objective: To evaluate both the individual and combined effects of acupressure and cognitive training on cognitive functions of older adults with MCI. Methods: One hundred and eighty older adults with MCI were recruited and randomly assigned to combined acupressure and cognitive training group (n=45), acupressure group (n=45), cognitive training group (n=45), or control group (n=45). Participants in the experimental groups received self-administered and group-based training sessions, while those in the control group received routine community education. The intervention lasted for six months. The cognitive functions of all the participants were assessed at multiple stages, including pre-intervention, at the end of the third and sixth months. Results: One hundred and fifty-one participants completed the study, and all participants analyzed in intervention groups completed at least 85% of all practice sessions recommended. Repeated measures analysis of variance of the scores of Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) at different time points among the four groups revealed that the group effect, time effect, and interaction effect were all significant (p < 0.01). Pairwise comparisons with Bonferroni correction showed that the scores of MMSE and MoCA in acupressure group, cognitive training group, and combined group were significantly raised compared with control group (p < 0.01). Compared with acupressure or cognitive training groups, the scores of MMSE and MoCA in combined group were significantly higher (p < 0.05). The scores of MMSE and MoCA in acupressure group had no significant differences with those in cognitive training group (p > 0.05). Conclusion: Acupressure and cognitive training both could improve the cognitive functions of older adults with MCI, and when used together, the effects were enhanced.